The Impact of Distance Learning Implementation in Early Childhood Education Teacher Profesional Competence - Andrisyah Andrisyah; Asih Nur Ismiatun (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
Covid-19 pandemic has an impact on early childhood education. This presents a major challenge for Early Childhood Education educators to improve their professional competence so that they can adapt to conditions in the current Covid-19 pandemic and respond to challenges in the era of society 5.0. The purpose of this study was to analyze the impact of distance learning on ECE teachers professional competencies. Sampling used cluster sampling techniques. This study involved 30 ECE teachers from three provinces on the island of Java. The method used is descriptive qualitative. Data collection techniques used open questionnaires containing indicators of ECE teachers professional competencies. The results showed that 30 ECE teachers in three provinces increased their professional competence especially in the use of technology that supports distance learning. support from government and institutions, is needed in improving teacher professional competence in the form of training that can reach all ECE teachers in Indonesia as a step towards facing the era of society 5.0.